Interheap GC - Dardis, Simon (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2015)
Garbage collection is the automation of memory management for computer programs. It is an important feature of both the Java and .NET environments, and it is a key component of the runtime system for many high level language implementations. A garbage collector’s critical tasks include recording program roots (global variables and thread stacks), finding all objects directly and transitively reachable from these roots, and finally reclaiming unused space.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin